Effect of Red Guava Juice Consumption on Hemoglobin Levels in Pregnant Women - Uswatun Awa Azizah; Febry Mutiariami Dahlan; Putri Azzahroh (KHD Production, 2024)
In Indonesia, the number of maternal deaths collected from the family health program records at the Ministry of Health in 2020 showed 4,627 deaths. This study aimed to determine the effect of red guava juice consumption on hemoglobin levels. This study used a quasi-experiment design method with a two-group pretest and posttest approach. The population in this study were anemic pregnant women in the first and third trimesters; the number of pregnant women with anemia in the last three months was 160, and the number of pregnant women with mild anemia was 57. Then, 30 pregnant women were taken as samples based on inclusion and exclusion criteria. Data collection using observation sheet. Data analysis was conducted using a T-dependent test, and results were presented using frequency distribution. The average hemoglobin level of the control group before the administration of Fe tablets was 9.80 gr/dl, and after consumption of Fe tablets was 10.45 gr/dl. The average hemoglobin level of the intervention group before giving Fe tablets + red guava juice was 9.64 gr/dl, and after consuming Fe tablets + red guava juice, it was 11.37 gr/dl. Statistical test results obtained p value = 0.000. Red guava juice consumption affects the hemoglobin levels of pregnant women. Pregnant women are recommended to consume Fe tablets regularly, accompanied by red guava juice, to increase hemoglobin levels.